Experimental Investigation on Two-Phase Rotating Detonation Fueled by Kerosene in a Hollow Directed Combustor - Xue, Sainan; Ying, Zhuojun; Ma, Hu; Zhou, Changsheng (Frontiers in Energy Research, 2022)
The operating characteristic of two-phase rotating detonation fueled by kerosene in a hollow combustor with the isolation section is experimentally studied. When the air mass flow rate is 1.5 kg/s, the equivalence ratio is 0.98, and the total temperature of the mixture is 650 K, the stable rotating detonation wave (RDW) is obtained, which verifies the feasibility of the designed two-phase rotating detonation combustor (RDC). It is found that there is a high-frequency oblique shock induced by the upstream rotating detonation wave in the isolation section. A series of experimental tests have been carried out by changing the total temperature of incoming air , which is an important factor affecting the initiation. When the equivalent ratio of reactants is between 0.950–1.152, a stable single-wave detonation is formed. With the increase of equivalent ratio, the time of detonation wave establishment decreases, the intensity and frequency of detonation wave increases, and the temperature of engine tail flame rises. The equivalent chamber pressure Δpφ was defined, and the curve of the performance of the RDC with the equivalent ratio was obtained. The velocity of the RDW increases with the increase of equivalent ratio, and the chamber pressure has an optimal value, a higher or lower equivalent ratio will lead to the decrease of equivalent chamber pressure and the combustion chamber performance.